The effect of financial leverage and market size on stock returns on the Bursa Malaysia stock exchange: evidence from the consumer product sector / Ismul Azam Suhaimi - Suhaimi, Ismul Azam (2017)
Numerous studies has been conducted by many researchers regarding to the stock returns (SR), market size (MS) and financial leverage (FLE) but only few who has combined these variables to verify whether these variables are inter-connected between each other. Due to the less number of studies conducted regarding this matter, the current study seeks to explain and thus investigates the effect of financial leverage and market size of selected stocks on stock returns. Ordinary Least Square (OLS) regression methods will be used to model the relationship between the dependent variable and the independent variables. Along the line of the aim of this study to prove whether those variable MS and FLE are directly interrelated with SR this study used all companies listed on the consumer product sector under Bursa Malaysia for five (5) years period starting 2011 until 2015. The secondary data are collected by using an appropriate data stream and from the annual financial reports covering the five years period. General results shows that individually market size and financial leverage did have impact on stock returns.